AJAG 2019
DOI: 10.17576/ajag-2019-12-05
|View full text |Cite
|
Sign up to set email alerts
|

Beneish Model, Corporate Governance and Financial Statements Manipulation

Abstract: This paper examined corporate governance and financial statements manipulation in Nigeria, using the Beneish model. To this end, the Beneish Model was employed to predict the likelihood of financial statements manipulation among the companies in Nigeria while the role of corporate governance variables to this manipulation was examined, using logistic regression analysis. In specific terms, the corporate governance variables of Board Composition, Board Gender Composition, Audit Committee Composition, and Board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…An AQI variable value greater than 1 can signal the presence of financial fraud. AQI has a higher value when accountants resort to revaluation techniques of assets/fixed assets, research and development and advertising costs are capitalized as intangible assets (Ibadin and Aimienrovbiye, 2019). The outcome of the last techniques might be to increase the assets while preserving the profitability of the company by using the manipulation techniques (Ibadin and Aimienrovbiye, 2019).…”
Section: Gross Margin Index (Gmi)mentioning
confidence: 99%
See 1 more Smart Citation
“…An AQI variable value greater than 1 can signal the presence of financial fraud. AQI has a higher value when accountants resort to revaluation techniques of assets/fixed assets, research and development and advertising costs are capitalized as intangible assets (Ibadin and Aimienrovbiye, 2019). The outcome of the last techniques might be to increase the assets while preserving the profitability of the company by using the manipulation techniques (Ibadin and Aimienrovbiye, 2019).…”
Section: Gross Margin Index (Gmi)mentioning
confidence: 99%
“…AQI has a higher value when accountants resort to revaluation techniques of assets/fixed assets, research and development and advertising costs are capitalized as intangible assets (Ibadin and Aimienrovbiye, 2019). The outcome of the last techniques might be to increase the assets while preserving the profitability of the company by using the manipulation techniques (Ibadin and Aimienrovbiye, 2019). In short, a high value of this variable indicates the presence of creative accounting/fraud by using excessive capitalization of expenditure (Ibadin and Aimienrovbiye, 2019…”
Section: Gross Margin Index (Gmi)mentioning
confidence: 99%
“…In Nigeria Ibadin and Ehigie (2019) found that Beneish M-score was able to predict FSM by listed companies and Hasan et al, (2017) using the Beneish M-score found that companies from Asian countries were significantly involved in FSM. In Indonesia Ratmono et al, (2020) used the Dechow F-score and Beneish M-score and found that both tools were able to detect FSM.…”
Section: Empirical Review and Hypothesis Development Forensic Account...mentioning
confidence: 99%
“…An independent board can be a useful company governance tool for improving financial reporting quality. According to recent studies, financial statement fraud has a negative association with board independence (Ibadin & Ehigie, 2019;Razali & Arshad, 2014;Anichebe, Agbomah, & Agbagbar, 2019;Nasir, Ali, & Ahemed, 2018). In contrast, from the standpoint of stewardship theory, inside directors have the potential to perform better than outside directors since they have a greater understanding of the business strategies and direction.…”
Section: Board Independencementioning
confidence: 99%
“…Similarly, other research has found that independent audit committee members' lack of understanding about the company can cause them to be unaware of internal control weaknesses and increase the likelihood of not identifying mistakes in financial information (Ahmad-Zaluki & Wan-Hussin, 2010). Prior literature indicates that there is no meaningful association between audit committee independence and earnings management (Uwuigbe et al, 2019;Ibadin & Ehigie, 2019;Oussii & Taktak, 2017;Yew, 2013).…”
Section: Audit Independencementioning
confidence: 99%